2021
DOI: 10.1093/ofid/ofab352
|View full text |Cite
|
Sign up to set email alerts
|

Postacute Sequelae of SARS-CoV-2 Infection and Impact on Quality of Life 1–6 Months After Illness and Association With Initial Symptom Severity

Abstract: Background Individuals with coronavirus disease 2019 (COVID-19) may have persistent symptoms following their acute illness. The prevalence and predictors of these symptoms, termed post-acute sequelae of SARS-CoV-2 (PASC), are not fully described. Methods Participants discharged from an outpatient telemedicine program for COVID-19 were emailed a survey (1-6 months after discharge) about ongoing symptoms, acute illness severity… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Few studies reported brain fog prevalence separately, and data may range from 2% to 10% [ 60 , 61 ]. However, several studies described difficulties that might resemble brain fog, but under different denominations, such as difficulties in daily activities [ 62 , 63 ], mental slowness [ 64 ], mental fog [ 60 , 65 ], difficulty or problems with thinking [ 66 , 67 ]. This variability in naming corresponds to great variability in prevalence data, ranging from 10% to 68%.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies reported brain fog prevalence separately, and data may range from 2% to 10% [ 60 , 61 ]. However, several studies described difficulties that might resemble brain fog, but under different denominations, such as difficulties in daily activities [ 62 , 63 ], mental slowness [ 64 ], mental fog [ 60 , 65 ], difficulty or problems with thinking [ 66 , 67 ]. This variability in naming corresponds to great variability in prevalence data, ranging from 10% to 68%.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were recruited online, and it is possible that those who developed long COVID are more invested in participating, potentially inflating the number of individuals with the syndrome, although our rates of long COVID are notably consistent with other reports. [6][7][8][9][10] We also did not have COVID-19 positivity confirmed for all participants; however, we excluded participants who did not report a positive PCR-test, a clinician diagnosis, or smell/taste loss (which is the strongest indicator of COVID-19 positivity), 21 minimizing the likelihood of including participants with no SARS-CoV-2 exposure. The cross-sectional design also limits our ability to determine causality, as is the case in any research examining the impact of childhood trauma in adults.…”
Section: Limitationsmentioning
confidence: 99%
“…Female sex, older age, higher body mass index (BMI), greater number of symptoms during acute illness, chemosensory impairment, and diarrhea are identified as predictors of long COVID. 6-9,12-15…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations